Fluid, Electrolyte and Acid-Base Disorders Clinical Evaluation and Management - Reddi, Alluru S. (Springer International Publishing, 2018)
Expanded with six additional chapters and new study questions, this updated edition provides a clear and concise understanding of the fundamentals of fluid, electrolyte and acid-base disorders that are frequently encountered in clinical practice. Each chapter follows a standard format that begins with pertinent basic physiology followed by its clinical disorder. Cases for each fluid, electrolyte and acid-base disorder are discussed, along with board-type questions with explanations to increase the knowledge for the clinician. Practical and clinically oriented, this book is a handy reference for practicing physicians, students, residents and fellows.